The Influence of Sound Slide Learning Media on Improving Student Learning Outcomes in Integrated Social Studies at SMP Negeri Satap Sinairusi MBD - Pinoa, Wiclif Sephnath; Naitioy, Meliga; Leuwol, Ferdinand Salomo (JENDELA PENGETAHUAN, 2024)
Sound Slides or sound slides are an innovation in learning that can be used as a learning medium and are effective in helping students understand abstract concepts to become more concrete (concretizing something that is abstract). Says that learning outcomes are changes in individual behavior which include the cognitive, affective and psychomotor domains. The learning outcomes referred to in this research are the changes obtained by students in completing the learning program through audio-visual learning media. This research was carried out at Satap Sinairusi MBD State Middle School for one month using this research method, namely quasi-experiment or quasi-experiment. Quasi Experiment has a control group, but it cannot function fully to control the variables that influence the implementation of the experiment, this is because the group used is a pre-existing group. Therefore, quasi experiments are used if it is difficult to get a control group. The learning outcomes of students from the experimental class experienced major changes after using sound slide learning media when compared to the control class which did not use sound slide learning media. This proves that the sound slide learning media has an effect on student learning outcomes in social studies subjects.